2015
DOI: 10.4103/1008-682x.150253
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor gamma signaling in human sperm physiology

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a member of the PPARs, which are transcription factors of the steroid receptor superfamily. PPARγ acts as an important molecule for regulating energy homeostasis, modulates the hypothalamic-pituitary-gonadal (HPG) axis, and is reciprocally regulated by HPG. In the human, PPARγ protein is highly expressed in ejaculated spermatozoa, implying a possible role of PPARγ signaling in regulating sperm energy dissipation. PPARγ protein is also expressed in Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…PPARG has a broad ligand binding spectrum, including unsaturated fatty acids, eicosanoids, and the prostaglandin PGJ 2 43 . In the human testis, PPARG protein is found in Sertoli cells and in germ cells (spermatocytes and spermatozoa) 44 . However, information available in the human Protein Atlas database 45 also indicates interstitial/extratubular PPARG/ Pparg expression.…”
Section: Discussionmentioning
confidence: 99%
“…PPARG has a broad ligand binding spectrum, including unsaturated fatty acids, eicosanoids, and the prostaglandin PGJ 2 43 . In the human testis, PPARG protein is found in Sertoli cells and in germ cells (spermatocytes and spermatozoa) 44 . However, information available in the human Protein Atlas database 45 also indicates interstitial/extratubular PPARG/ Pparg expression.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CB1 and PLIN1 in the Shandong black cattle was significantly higher than it was in the Luxi cattle, but the PPARγ2 and HSL expression levels were significantly lower than they were in the Luxi cattle. Previous studies have shown that the rate-limiting enzyme of triacylglycerol (tag) catabolism in hormone-sensitive lipase (HSL) tissue, together with triacylglycerol lipase and monoacylglycerol lipase, regulates the storage of fat in muscle ( Liu et al, 2015 ). PPARγ2 plays an important role in regulating lipid metabolism, adipogenesis, insulin sensitivity, inflammatory response, cell growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…PPARG has a broad ligand binding spectrum, including unsaturated fatty acids, eicosanoids and the prostaglandin PGJ2 41 . In the human testis, PPARG protein is found in Sertoli cells and in germ cells (spermatocytes and spermatozoa) 42 . However, information available in the human Protein Atlas database 43 also indicates interstitial/extratubular PPARG/Pparg expression.…”
Section: Insl3 and Ppargmentioning
confidence: 99%